The experiences of psychiatric patients, their caregivers and companions in upholding patient dignity during hospitalization: A qualitative study - Amirahmad Shojaei; Yosra Raziani; Colleen Bernstein; Ali Asgari; Farshid Alazmani‐Noodeh; Mohammadreza Arab; Hadi Ranjbar (Wiley, 2023)
Abstract Introduction The quality of care and patient satisfaction is closely linked with dignity, which is a crucial component of therapy and care. However, there is very little study on dignity in the context of mental health care. Planning for ongoing patient care might benefit from an understanding of the notion of dignity by exploring the experiences of patients, caregivers and companions of patients who have a history of hospitalization in mental health institutions. To retain patients' dignity while they were being treated in mental wards, this study sought to understand the experiences of patients, caregivers and companions of patients. Materials and Methods This investigation was qualitative. Semistructured interviews and focus groups were utilized to collect the data. The purposeful sampling method was employed for participant recruitment, which continued until data saturation. Two focus group discussions and 27 interviews were conducted. Participants included 8 patients, 2 patients' family members (companions), 3 psychologists, 4 nurses and 11 psychiatrists. Two focus group discussions were held with seven family members or companions of patients. Thematic analysis was used for data analysis. Results The primary theme that emerged was the infringement of patients' dignity, through negative guardianship, dehumanization and violations of their rights. Subthemes included dehumanization, worthlessness and namelessness, patient rights violations and stripping patients of authority. Conclusion Our results suggest that, regardless of the severity of the illness, the nature of psychiatric illness significantly compromises patients' dignity. Mental health practitioners, due to their sense of guardianship, may unintentionally treat patients with mental health disorders, thus compromising the patient's dignity. Patient or Public Contribution The research team's experiences as a psychiatrist, doctor and nurse informed the study's objectives. Nurses and psychiatrists who work in the healthcare industry designed and conducted the study. The primary authors, who are healthcare providers, collected and analysed the required data. Furthermore, the entire study team contributed to the writing of the manuscript. Study participants were involved in the data collection and analysis.